Rapid heartbeat, but dry palms: reactions of heart rate and skin conductance levels to social rejection - Iffland, Benjamin; Sansen, Lisa M.; Catani, Claudia; Neuner, Frank (Frontiers in Psychology, 2014)
Background: Social rejection elicits negative mood, emotional distress and neural activity in networks that are associated with physical pain. However, studies assessing physiological reactions to social rejection are rare and results of these studies were found to be ambiguous. Therefore, the present study aimed to examine and specify physiological effects of social rejection. Methods: Participants (N = 50) were assigned to either a social exclusion or inclusion condition of a virtual ball-tossing game (Cyberball). Immediate and delayed physiological (skin conductance level and heart rate) reactions were recorded. In addition, subjects reported levels of affect, emotional states and fundamental needs. Results: Subjects who were socially rejected showed increased heart rates. However, social rejection had no effect on subjects’ skin conductance levels. Both conditions showed heightened arousal on this measurement. Furthermore, psychological consequences of social rejection indicated the validity of the paradigm. Conclusions: Our results reveal that social rejection evokes an immediate physiological reaction. Accelerated heart rates indicate that behavior activation rather than inhibition is associated with socially threatening events. In addition, results revealed gender-specific response patterns suggesting that sample characteristics such as differences in gender may account for ambiguous findings of physiological reactions to social rejection.